Acute Shunt Failure Due to Perforation of Ventriculoperitoneal Shunt Tubing during Percutaneous Gastrostomy - Vivas, Andrew C. (ACG Case Rep J, 2017)
The placement of a percutaneous endoscopic gastrostomy (PEG) in a patient with a pre-existing ventriculoperitoneal shunt is generally regarded as safe. A critical but often overlooked technical consideration is confirmation of the course of the distal shunt tube prior to PEG insertion. We present the case of a 4-month-old male infant with shunted hydrocephalus who experienced shunt malfunction due to perforation of the distal shunt tubing after PEG placement.